MODERN PROBLEMS OF FORMATION AND DEVELOPMENT OF THE TAX RELATIONS IN THE CRIMEA AND SEVASTOPOL - E. Gulkova; M. Tipalina (Вестник университета, 2016)
The authors systematically reviewed special regimes of activity in the Republic of Crimea, including a special tax regime. The authors selected problems in the field of taxation in the regions: disputes between tax authorities and organizations upon payment of taxes for 2014; taxation of organizations that have not been re-registered tax burden, assessment of the effectiveness of tax benefits.